Influence of ‘El Niño, Southern Oscillation’ on the yield of rainfed corn in Nayarit - Bojórquez-Serrano, José Irán; Vidal-Martínez, Víctor Antonio; Álvarez-Bravo, Arturo; Coutiño-Estrada, Bulmaro (Revista Mexicana de Ciencias Agrícolas, 2020)
In Mexico, the phenomenon of El Niño Southern Oscillation (ENSO) affects weather conditions and consequently on the behavior of crops, especially rainfed corn. For the rainfed corn-producing region in the state of Nayarit, there is no information available to measure this influence. The objective of this research was to know the impact of the ENSO phases on some meteorological variables during the vegetative cycle of corn and the degree of vulnerability on grain yield. A 15-year phenological database of evaluation records of commercial maize varieties were used. Quantifying the rainfall, wet days, potential evapotranspiration and degree days of development during the vegetative cycle of the crop, grouping the data by phase of the ENSO ‘El Niño’, ‘Neutral’ and ‘La Niña’. Joined with an analysis of yield and its vulnerability to climate variability. The influence on precipitation and air temperature (degree days of development) was widely identified, which are important for the development of maize in storm. In ‘Niña’ events, precipitation is 28.6% higher than in the ‘Niño’ phase, contrary to the degree days of development, where in the ‘Niño’ phase it accumulates 6.3% more than in ‘Neutral’ or ‘Niña’. This explains the yield of early varieties in the ‘Niño’ phase (greater than 8 t ha-1) and makes it clear how the vulnerability of this crop can decrease if adequate seed is available for each phase of the ENSO.